2022
DOI: 10.3390/medicina58081125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Influencing Personal Exposure to Air Pollution on Main Roads in Bogota: A Mixed-Method Study

Abstract: Background and Objectives: Particulate Matter (PM), particles of variable but small diameter can penetrate the respiratory system via inhalation, causing respiratory and/or cardiovascular diseases. This study aims to evaluate the association of environmental particulate matter (PM2.5) and black carbon (BC) with respiratory health in users of different transport modes in four roads in Bogotá. Materials and Methods: this was a mixed-method study (including a cross sectional study and a qualitative description of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
1
6
0
2
Order By: Relevance
“…El estudio encontró que existen elementos en el entorno que son capaces de influir en las concentraciones de PM2.5, entre las que se destacan la ubicación cercana a parqueaderos y avenidas. Estos hallazgos son coincidentes con lo reportado en la literatura donde se sostiene que dentro de los principales determinantes de la exposición personal se encuentran el tipo de vehículos y la cercanía de las ciclorrutas a las fuentes emisoras móviles (15,21).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El estudio encontró que existen elementos en el entorno que son capaces de influir en las concentraciones de PM2.5, entre las que se destacan la ubicación cercana a parqueaderos y avenidas. Estos hallazgos son coincidentes con lo reportado en la literatura donde se sostiene que dentro de los principales determinantes de la exposición personal se encuentran el tipo de vehículos y la cercanía de las ciclorrutas a las fuentes emisoras móviles (15,21).…”
Section: Discussionunclassified
“…And Health Effects in Microenvironments in Bogotá) realizado por el Instituto Nacional de Salud (INS), la Universidad Manuela Beltrán y la Universidad de los Andes, se ha logrado llevar a cabo la caracterización de los factores que determinan la exposición a contaminantes en el aire en cinco rutas de la ciudad de Bogotá, así como evaluar el efecto en el corto plazo sobre la salud respiratoria de usuarios de transporte motorizado y no motorizado (14)(15)(16).…”
Section: Desde El Proyecto Ithaquita (Air Contaminationunclassified
“…Nevertheless, there is limited evidence regarding the short-term effects of PM 2.5 and eBC exposure on healthy participants. Findings from the ITHACA study, conducted in four corridors of Bogota and involving three different transport modes, indicated that PM 2.5 and eBC concentrations were the highest in buses and minivans compared to bicycles (p < 0.05) [11]. However, the ITHACA study did not observe any effects on spirometry volumes among the participants, raising the question of whether spirometry is sensitive enough to evaluate the short-term effects of PM 2.5 and eBC on lung function [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies provide solid evidence of an association between high concentrations of air pollution and mortality 3 or other health outcomes, such as increased ischaemic heart disease, strokes, infections of the lower respiratory tract, asthma or chronic obstructive pulmonary disease 4 and mental health indicators, such as psychological stress, symptoms of depression or suicide. [5][6][7][8][9] Brain damage caused by air pollution seems to be associated with dementia and with weakened cognitive functioning throughout the life course. 10,11 Exposure to air pollutants has potentially harmful effects from the earliest stages of life with negative effects on pregnancies as well as long-term effects that affect susceptibility to disease later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Risk awareness is also crucial for citizens to engage in collective action (eg, through different forms or degrees of activism and to support/call for policy initiatives initiated by local, regional or national governments). 7,13 Therefore, understanding how individuals perceive air pollution, is crucial for combating it and to improve public health.…”
Section: Introductionmentioning
confidence: 99%